Characteristics and outcomes of multisystem inflammatory syndrome in children: A multicenter, retrospective, observational cohort study in Mexico - Yamazaki-Nakashimada, Marco Antonio; Márquez-González, Horacio; Miranda-Novales, Guadalupe; Neme Díaz, Gonzalo Antonio; Prado Duran, Sandhi Anel; Luévanos Velázquez, Antonio; Castilla-Peon, Maria F.; González-García, Nadia; Sánchez Duran, Miguel Alejandro; Márquez Aguirre, Martha Patricia; Villasis-Keever, Miguel Angel; Aragón Nogales, Ranferi; et al. (Frontiers in Pediatrics, 2023)
Multisystem inflammatory syndrome in children associated with coronavirus disease 2019 (MIS-C), a novel hyperinflammatory condition secondary to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, is associated with severe outcomes such as coronary artery aneurysm and death. This multicenter, retrospective, observational cohort study including eight centers in Mexico, aimed to describe the clinical characteristics and outcomes of patients with MIS-C. Patient data were evaluated using latent class analysis (LCA) to categorize patients into three phenotypes: toxic shock syndrome-like (TSSL)-MIS-C, Kawasaki disease-like (KDL)-MIS-C, and nonspecific MIS-C (NS-MIS-C). Risk factors for adverse outcomes were estimated using multilevel mixed-effects logistic regression. The study included 239 patients with MIS-C, including 61 (26%), 70 (29%), and 108 (45%) patients in the TSSL-MIS-C, KDL-MIS-C, and NS-MIS-C groups, respectively. Fifty-four percent of the patients were admitted to the intensive care unit, and 42%, 78%, and 41% received intravenous immunoglobulin, systemic glucocorticoids, and anticoagulants, respectively. Coronary artery dilatation and aneurysms were found in 5.7% and 13.2% of the patients in whom coronary artery diameter was measured, respectively. Any cause in-hospital mortality was 5.4%. Hospitalization after ten days of symptoms was associated with coronary artery abnormalities (odds ratio [OR] 1.6, 95% confidence interval [CI] 1.2–2.0). Age ≥ 10 years (OR 5.6, 95% CI 1.4–2.04), severe underlying condition (OR 9.3, 95% CI 2.8–31.0), platelet count < 150,000/mm3 (OR 4.2, 95% CI 1.2–14.7), international normalized ratio > 1.2 (OR 3.8, 95% CI 1.05–13.9), and serum ferritin concentration > 1500 mg/dL at admission (OR 52, 95% CI 5.9–463) were risk factors for death.